MAKNA IBADAH DALAM KEHIDUPAN SOSIAL MAHASISWA MUSLIM - Rossa, Julia; Eka Septi Anggraini, Adelia; Harianto, Jimi (As-Sulthan Journal of Education, 2026)
Worship in the social aspect of Muslim student life has frequently been perceived as confined to vertical rituals (hablun minallah) rather than social practices (hablun minannas). This research aims to analyze how Muslim students interpret worship, particularly prayer, fasting, and charity, and how this interpretation is reflected in their social interactions and student activities. Using a qualitative approach with a case study design at three universities, data were collected through in-depth interviews, participant observation, and documentation, and then analyzed thematically. The research findings indicate that students who comprehensively understand worship tend to have higher levels of empathy, social care, and a sense of collective responsibility. Worship performed with reflective awareness brings inner peace and fosters social piety, such as honesty in organizations, fairness toward others, and active participation in philanthropic activities and community service. This finding confirms that worship is not merely an individual spiritual obligation but rather an important foundation in shaping social ethics and building a civilized, inclusive, and harmonious campus culture.